EFFECTS OF FO2, FS2, TEMPERATURE, AND MELT COMPOSITION ON FE-NI EXCHANGE BETWEEN OLIVINE AND SULFIDE LIQUID: IMPLICATIONS FOR NATURAL OLIVINE-SULFIDE ASSEMBLAGES - Brenan J.M. (My University, 2003)
The apparent equilibrium constant for the exchange of Fe and Ni between coexisting olivine and sulfide liquid (KD = (XNiS/XFeS)liquid/(XNiSi12O2/XFeSi12O2)olivine; Xi = mole fraction) has been measured at controlled oxygen and sulfur fugacities (fO2 = 10−8.1 to 10−10 and fS2 = 10−0.9 to 10−1.7) over the temperature range 1200 to 1385°C, with 5 to 37 wt% Ni and 7 to 18 wt% Cu in the sulfide liquid. At log fO2 of −8.7 ± 0.1, and log fS2 of −0.9 to −1.7, KD is relatively insensitive to sulfur fugacity, but comparison with previous results shows that KD increases at very low sulfur fugacities. KD values show an increase with the nickel content of the sulfide liquid, but this effect is more complex than found previously, and is greatest at log fO2 of −8.1, lessens with decreasing fO2, and KD becomes independent of melt Ni content at log fO2 ≤ −9.5. The origin of this variation in KD with fO2 and fS2 is most likely the result of nonideal mixing of Fe and Ni species in the sulfide liquid. Such behavior causes activity coefficients to change with either melt oxygen content or metal/sulfur ratio, effects that are well documented for metal-rich sulfide melts.